Mitigation and management plans should consider all anthropogenic disturbances to fauna - Cross, Sophie; Cross, Adam; Tomlinson, Sean; Clark-Ioannou, Sophia; Nevill, Paul; Bateman, Bill (2021)
The direct impacts of anthropogenic habitat loss on fauna have attracted considerable global research focus. However, it is not only these overt impacts of human activities that are contributing to the global biodiversity crisis. Other disturbances, such as artificial light, anthropogenically generated noise, dust, vibrations, and physical visual disturbances (e.g., foreign objects such as Unmanned Aerial Vehicles - UAVs) may be subtle or indirect, yet capable of creating significant impacts to fauna. These disturbances have previously been termed ‘enigmatic impacts’, suggesting they may be difficult to quantify or address. While there has been little research focus towards the mitigation or remediation of these impacts in conservation and restoration planning, a growing body of literature demonstrates that they can be disruptive and damaging to animal populations at multiple spatial and temporal scales. Here, we present a global review of the empirical evidence for disturbances (excluding direct habitat loss) that result from anthropogenic activities, developments, and industries, which are deleterious to the natural ecology of fauna species or communities. Although the impacts of disturbances such as vibrations and visual disturbances on fauna have attracted little research focus, disturbances created by human activities are clearly capable of causing significant disruptions and adverse impacts to fauna. Understanding how such disturbances impact fauna is critical to returning functional and biodiverse fauna communities to landscapes and environments that have been impacted or degraded by human activities.